Determination of Heavy Metals and Comparison to Gross Radioactivity Concentration in Soil and Sediment Samples of the Bendimahi River Basin (Van, Turkey) - Zorer, Oezlem Selcuk; Ceylan, Hasan; Dogru, Mahmut (Springer International Publishing Ag, 2009)
An investigation of radioactivity and some heavy metal distribution in soil and sediment of the river basin (Bendimahi River, Van-Turkey) was conducted in two seasons of 2005. The samples of soil and sediment were collected from the basin and investigated for concentrations of some heavy metal and natural radioactivity. Concentrations of Pb, Cr, Mn, Fe, Co, Cu, Zn and Cd have been determined by Atomic Absorption Spectrometry (AAS), gross-alpha and gross-beta activity concentrations have been obtained by using gas-flow proportional counter in nuclear spectroscopic system. Correlation analysis was made for radioactivity and heavy metal concentrations and the Pearson correlation coefficients between gross-alpha and gross-beta radioactivity and heavy metal were determined.
Keywords: Gross-alpha; Gross-beta; Heavy metal; Natural radioactivity; Sediment; Soil